2020
DOI: 10.3390/w12061719
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Fuzzy Analytic Hierarchy Process for the Allocation of Water Rights to Industries in Northeast China

Abstract: To facilitate water management and efficient utilization of water resources, the allocation of water rights to individual industries must be underpinned by a rational and defensible process. This study aimed to develop an improved fuzzy analytic hierarchy process method of allocating water rights to different industries and focused on Qing’an County, northeast China as a case study. An evaluation index system for allocation of initial water rights was established, and incorporated physiographic, societal, econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In An Giang the Northeast and the Southeast regions have bad quality water due to high Arsenic amount in water caused in monsoon season due to sediment deposition. Whereas, it also has bad ground water quality due to the combined effect of human and natural activities [2,15]. In areas, wherever groundwater is extracted for irrigation it had high values of GWQI links with high Arsenic content.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In An Giang the Northeast and the Southeast regions have bad quality water due to high Arsenic amount in water caused in monsoon season due to sediment deposition. Whereas, it also has bad ground water quality due to the combined effect of human and natural activities [2,15]. In areas, wherever groundwater is extracted for irrigation it had high values of GWQI links with high Arsenic content.…”
Section: Related Workmentioning
confidence: 99%
“…The unsuitable use Groundwater may be a significant issue as the rapidly increasing population and also the expansion of social economy has incremented the utilization of water resources [15]. Due to which there is a disparity between accessible water and demanded water in few areas.…”
Section: Related Workmentioning
confidence: 99%
“…Alphonce [ 50 ] suggested the potential application of AHP in agricultural decision-making such as resource allocation, subsistence farming, or determination of the production technology. Other studies focus on the development of decision-making models; to select the most appropriate irrigation method [ 51 , 52 ], to select irrigation water optimal allocation [ 53 , 54 ], for the assessment of irrigation water quality [ 55 ], for the evaluation of agricultural water management [ 56 ], and in the improvement of irrigation projects [ 57 ]. However, no AHP studies have been found aimed at the construction of an integrative and comprehensive indicator of irrigation efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of satellite-based remote sensing techniques, gross primary production and evapotranspiration provided by MODIS products were used to analyze spatial and temporal patterns of WUE, as well as its relationships with environmental factors [33,43]. Compared to other evaluation methods, the fuzzy evaluation method has the advantage of clear results and a strong system, and it is mostly adopted to solve these problems that are fuzzy and difficult to quantify, especially non-deterministic problems [44]. Moreover, fuzzy mathematics is capable of taking fuzzy objects to be examined and fuzzy concepts reflecting fuzzy objects as certain fuzzy sets, and establishing appropriate membership functions [45].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from a single evaluation method, some coupled methods were proposed in assessment of agricultural WUE, because these methods are likely to take advantage of multiple evaluation methods [46]. Taking the fuzzy analytic hierarchy process (FAHP) method as an example, the analytic hierarchy process is flexible to applicate and suitable for handling complex real-life problems, while fuzzy decision theory can make up for deficiencies and limitations, including uncertainty and poor reliability of determining index weights [44]. In spite of the good performance of the fuzzy analytic hierarchy process method, there is still room to deal with the nonlinear problem [47].…”
Section: Introductionmentioning
confidence: 99%